Fontes de energia associadas a um hepatoprotetor na dieta de vacas em lactação confinadas. - Pinheiro, Jessyca Karen (2020)
The aim of this study was to evaluate the effects of energy sources associated with a hepatoprotector on the performance and metabolism of confined lactating cows. Two studies were carried out, which used 16 crossbred Holstein x Gir cows in the middle third of lactation, with an average body weight of 553 ± 85 kg, distributed in a quadratic quadruple 4x4 experimental design in a 2x2 factorial arrangement. The treatments consisted of a diet with or without the inclusion of the commercial hepatoprotector, and variation of ground corn or citrus pulp as energy sources. In the first study, which evaluated the performance and nutrient partitioning of lactating cows, it was observed that: dry matter consumption, milk production, 4% fat-corrected milk were higher (P= 0,001) in corn diets ground as a source of energy. The fat content of milk was higher (P= 0,049) in diets with citrus pulp. There was a reduction (P<0,05) in the crude protein content in the milk of cows that received the hepatoprotector in the diet. The hepatoprotector favored a higher (P=0,038) nitrogen balance in cows. In the second study, which evaluated the metabolic status of lactating cows, it was found that: ground corn as an energy source provided higher (P<0,05) serum concentrations of glucose, HDL- cholesterol and globulins. Whereas, -hydroxybutyrate (BHB), non-esterified fatty acids (AGNE), total cholesterol, albumin and aspartate aminotransferase (AST) presented the highest concentrations (P<0,05) in diets with citrus pulp. There was an interaction (P= 0,004) between time and the inclusion of the hepatoprotector in the plasma LDL- cholesterol concentration. However, both studies did not find an interaction between energy sources and the hepatoprotector for the variables of performance, nutrient partition and metabolic status. Corn as a source of energy in the diet boosted milk production and the synthesis of glycogenic precursors. Meanwhile, the citrus pulp changed the lipid status and the composition of the milk by increasing the fat content. The hepatoprotector affected the protein content in milk, improved the nitrogen balance and contributed to postprandial increase in serum LDL-cholesterol concentrations in confined lactating cows.